O conhecimento sobre finalidades educativas da inclusão escolar de pessoas com deficiência em periódicos nacionais (2014-2019) - Elmescany, Ilma Aparecida dos Santos (2021)
This dissertation linked to the research line Theories of Education and Pedagogical Processes, of the Post-Graduate Program in Stricto Sensu in Education, of the Pontifical Catholic University of Goiás, established as research object the analysis of the educational purposes of the school inclusion of people with disabilities. It is supported by theorists who study educational purposes at school, in the light of historical-dialectical materialism, specifically in the concept of educational purposes described by Yves Leonir. With the assumption that academic works that address the school inclusion of people with disabilities, in some way, can portray philosophical and political concerns and positions, indicating possible educational purposes, this study seeks to respond as the journals in the field of education, which have function of socializing the knowledge produced in the academy, have you discussed the educational purposes of school inclusion of people with disabilities? To apprehend the problem, it was decided to carry out a literature review, with the main objective of identifying and analyzing the educational purposes of school inclusion of people with disabilities, published in articles published in national journals in the field of education from 2014 to 2019. The search for works took place in the theses and dissertations database of the Coordination for the Improvement of Higher Education Personnel - Capes. Based on the selection criteria, 14 articles were reached. The content of the articles was analyzed from the categories defined in the theoretical framework as well as from the categories that emerged during the analysis process. The interpretation identified the explicit or implicit presence of the following educational purposes, presented by Leonir (2013): Identity, Difference, Equality, Education as a human right, Cognitive development, Personal development, Individual development, Citizenship, Lifelong learning , Democracy, linked to two theoretical-methodological perspectives: sociocultural and cultural-historical. The study allowed us to infer that the analyzed production expresses the tension between educational purposes, which acquire singularities in the midst of neoliberal society, whose educational proposals incorporate the neotechnicist/economist conception to which human development and critical educational conceptions are submitted, specifically that of a historicalcultural perspective, according to which the educational purpose of a truly inclusive school is to promote the intellectual development of students, substantiated by the integration between school activities and contents carried out as a means for the development of skills and competences of an emancipatory nature